Trust among the Avatars: A Virtual World Experiment, with and without Textual and Visual Cues. - Atlas, Stephen; Putterman, Louis (Southern Economic Journal, 2011)
We invited "residents" of a virtual world who vary in real-world age and occupation to play a trust game with stakes comparable to "in-world" wages. In different treatments, the lab wall was adorned with an emotively suggestive photograph, a suggestive text was added to the instructions, or both a photo and text were added. We find high levels of trust and reciprocity that appear still higher for non-student and older subjects. Variation of results by treatment suggests that both photographic and textual cues influenced the level of trust but not that of trustworthiness.